PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS VIII SMP NEGERI 16 PADANG - Efrida Yanna Nasution (Jurnal Edukasi dan Penelitian Matematika, 2021)
Mathematical problem solving is one of several mathematical abilities that must be possessed by students as stated in the mathematics learning objectives in Permendikbud number 22 of 2016. However, students' mathematical problem solving abilities are still relatively low. One of the efforts that can improve students' mathematical problem solving skills is applying the Problem Based Learning model. The purpose of this study is to analyze and describe that the mathematical problem solving ability of students who learn to use the Problem Based Learning model is better than the mathematical problem solving abilities of students who learn by conventional learning.The type of research used in this study is a quasi-experimental and descriptive research with a Randomized Control Only Group Design research design. The population of this study is class VIII students of SMP Negeri 16 Padang in the academic year 2021/2022 with the research sample being students of class VIII.1 as the experimental class and students of class VIII.3 as the control class. The sampling technique was carried out by Simple Random Sampling, namely simple random sampling. Research data obtained from the final test of mathematical problem solving ability. Based on the results of the final test data analysis with a significance level (α) equal to 0.05, it was obtained that P-value = 0.000 where if P-value < then reject Ho. In other words, the mathematical problem solving ability of students who learn to use the Problem Based Learning model is better than the mathematical problem solving abilities of students who learn using conventional methods. Therefore, it can be concluded that there is an effect of applying the Problem Based Learning model on the mathematical problem solving ability of eighth grade students of SMP Negeri 16 Padang. Keywords – Problem Based Learning, Mathematical Problem Solving Ability